1987
DOI: 10.1136/adc.62.12.1224
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of height and weight at adolescence.

Abstract: SUMMARY A longitudinal study through puberty of the height and weight of 96 boys and 102 girls in schools in and around the city of Leeds was conducted. Data for height and weight and height and weight velocities are presented, which are based on chronological age and on age relative to the age of peak height velocity. Comparison was made with the Tanner standards: male puberty developed a little later but growth continued longer, so that the adult men were taller and heavier. Girls showed a similar timing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
10

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 11 publications
3
28
0
10
Order By: Relevance
“…There are likely to be bigger differences in body size (weight and height) between the younger and older boys than between the younger and older girls (Buckler & Wild, 1987). Finally, we found a significant main effect for sex for distance from the wall which post hoc comparisons indicated that distance was greater for boys than girls.…”
Section: Competition In 229 M Of Watersupporting
confidence: 54%
“…There are likely to be bigger differences in body size (weight and height) between the younger and older boys than between the younger and older girls (Buckler & Wild, 1987). Finally, we found a significant main effect for sex for distance from the wall which post hoc comparisons indicated that distance was greater for boys than girls.…”
Section: Competition In 229 M Of Watersupporting
confidence: 54%
“…In the studies by Marshall and Tanner [16,17] based on clinical criteria (as in this study) the average age of onset of puberty was 11.6 years in boys (n = 288) and 11.2 years in girls (n = 192), while TPG was 29.5 and 19.2 cm in boys and girls, respectively. In the British cohort investigated by Buckler and Wild [19] the age at puberty onset was 12.2 years with a TPG of 28.0 cm in boys (n = 128) and 11.1 years with a TPG of 21.0 cm in girls (n = 83), respectively. Ethnicity and secular developments may also impact on the timing and extent of pubertal growth [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Even in studies on growth and development in normal children, depending on the method used – visible appearance of pubertal stages [16,17,18,19] or the nadir of height velocity based on longitudinal growth analysis [20] – different time points of puberty onset and differences of the observed TPG were established. In the studies by Marshall and Tanner [16,17] based on clinical criteria (as in this study) the average age of onset of puberty was 11.6 years in boys (n = 288) and 11.2 years in girls (n = 192), while TPG was 29.5 and 19.2 cm in boys and girls, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although a deceleration of growth velocity before puberty is physiological, no significant change in height SDS before puberty is expected in normal children [16]. Growth during puberty, expressed as total height gain and growth velocity, was reduced when compared to normal subjects [12, 13], regardless of hypogonadism. Final height SDS was not significantly different from height SDS for CA at the beginning of puberty in patients with spontaneous puberty, while it was even improved in patients with induced puberty.…”
Section: Discussionmentioning
confidence: 99%
“…PHV was the highest growth velocity observed during a 6- to 12-month period from the start of puberty to final height. Buckler standards were used to evaluate PHV and PHG [12, 13]. …”
Section: Methodsmentioning
confidence: 99%